The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1984
DOI: 10.1016/s0022-5347(17)50210-4
|View full text |Cite
|
Sign up to set email alerts
|

Total Prostatectomy for Localized Prostatic Cancer

Abstract: Several treatment options currently are available for the patient with clinically localized carcinoma of the prostate and each has its proponents. Comparison of results between institutions becomes necessary to determine the relative value of these treatments, keeping in mind the absence of a suitable control group in any series. Such inter-institutional treatment comparisons are possible only if the patient compositions are similar in terms of age, grade and extent of disease. Comparisons of patients with sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
24
1
2

Year Published

1987
1987
2001
2001

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 187 publications
(31 citation statements)
references
References 15 publications
4
24
1
2
Order By: Relevance
“…Similar results have been reported following radical surgery (31). Therefore the early stage prostatic cancer, which has been radically treated, does not essentially increase the risk of death.…”
Section: Radiation Therapy Of Prostate Cancer Retrospective Studiessupporting
confidence: 83%
“…Similar results have been reported following radical surgery (31). Therefore the early stage prostatic cancer, which has been radically treated, does not essentially increase the risk of death.…”
Section: Radiation Therapy Of Prostate Cancer Retrospective Studiessupporting
confidence: 83%
“…The incidence of continence achieved in the present trial (97% of the total patient population without any instance of total incontinence) is in the range of the reported rates between 67 and 96%, with 0–35% of the patients demonstrating stress incontinence and 0–18% complaining of total incontinence in the literature [10, 12, 13, 14, 15, 16, 17, 18, 19]. The discrepancy between these rates might in part reflect differences in study design, patient population length and completeness of follow-up, methods for measuring incontinence, surgical proficiency and interviewers.…”
Section: Discussionmentioning
confidence: 69%
“…The major problems associated with radical prostatectomy are high rates of impotence and urinary incontinence, which can affect quality of life [12, 13]. However, Walsh [14]reported that with good nerve-sparing techniques, continence and potency rates should be high, resulting in excellent quality of life in patients with localized disease.…”
Section: Radical Prostatectomymentioning
confidence: 99%